Communication tools with intra-body sensors - Caldeira, João Manuel Leitão Pires (2015)
Over the years some medical studies have tried to better understand the internal behavior of human beings. Many researchers in this domain have been striving to find relationships between intra-vaginal temperature and certain female health conditions, such as ovulation and fertile period since woman’s intra-vaginal temperature is one of the body parameters most preferred in such studies. However, due to the lack of an appropriate technology, medical research devoted to studying correlations of such body parameters with certain woman’s body phenomena could not obtain improve on better results. The objective of this work falls in the creation of communication tools with intra-body sensors. These sensors must be able to collect intra-body parameters such as human core temperature. To reach this main objective the construction of a new intra-body sensor for acquisition and monitoring the intra-vaginal temperature is proposed. This novel intra-body sensor provides data collection that is used to studying the relation between temperature variations and female health conditions, such as anticipation and monitoring of the ovulation period, detection of pregnancy contractions, preterm labor prevention, etc. The novel sensor and his communication tools was tested and validated on hospitalized women as well as normal healthy women. Finally a medical team has attested to the accuracy, usability and performance of this novel intrabody sensor.